Post-Mortem Condemnations in Slaughterhouses: Analysis of Organs, Causes, and Economic and Sanitary Impacts in the Municipality of Cacoal, State of Rondônia (RO), Brazil (Research, Society and Development, 2025)
Sanitary inspections at beef slaughterhouses play a fundamental role in ensuring food safety and preventing zoonoses, ensuring that only products fit for consumption reach the market. Monitoring viscera and slaughtered carcasses provides valuable information on the health status of herds and reveals flaws in handling and slaughter practices. The most common condemnations involve the liver, kidneys, and lungs, organs most susceptible to contamination and pathological alterations. In addition to the impact on public health, these condemnations generate significant economic losses for slaughterhouses and producers, reinforcing the importance of good management practices, biosafety, and team training. Continuously recording the causes of condemnations allows for the improvement of production processes and contributes to regional health control. The study's main question is: "What are the most frequently condemned organs and viscera at a slaughterhouse in Cacoal, Rondônia, and their economic and health impacts?" The overall objective is to report and describe the condemnations observed during post-mortem inspections at a slaughterhouse located in Cacoal, Rondônia, during the month of July 2025, identifying the frequency and causes of these condemnations. This case report uses a descriptive and quantitative approach, developed based on the observation and analysis of data obtained from post-mortem inspections conducted at a slaughterhouse under state inspection services. Based on the results, it can be concluded that the proposed problem was fully addressed. The most frequent condemnations were concentrated in kidneys and livers, reflecting both sanitary factors of the industrial process and physiological aspects of the slaughtered animals. The consequences of these rejections are expressed not only in terms of direct economic losses but also as indicators of the effectiveness of the hygiene controls and inspection practices applied at the establishment.